Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

Synergistic effects of co-pyrolyzed rice straw/non-woven fabric biochar on soil enhancement and rice growth promotion - Shuo Su; Jiachen Zhu; Tian Xie; Zhihua Zhang; Yi Zhu; Yu Xie; Yuting Ran; Lingling Yao; Jie Qin; Jing Huang; Junxin Zhou; Zhi Zhou; et al. (Paddy and Water Environment, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Zero-valent iron induced redox oscillations: Mechanisms of dynamic Fe(II) promote ferrihydrite transformation and lattice immobilization for Pb, Cd, and As - Zhi Jiang; HongZhen Ran; Lin Yu; PengWei Zhao; Weichun Yang (Chemical Engineering Journal, 2026)

Late Mesozoic exhumation of metamorphic core complexes from the Xiaoqinling to Dabie orogen, central China: a record of Paleo-Pacific slab rollback - Wan-Shan Lei; Yu Duan; Zhi-Qiang Liu; Ran Wang; Hai-Dong Zhang; San-Zhong Li (International Geology Review, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

A highly fractionated origin for the Yanshanian water-rich A-type granite in the Southern Great Xing’an Range, NE China: Insights from zircon and monazite geochemistry - Zi-Yi Wang; Hao Yang; Hao-Ran Wu; Zhi-Chao Zhang; Zheng Ji; Yu Dong; Wen-Chun Ge (Journal of Asian Earth Sciences, 2025)

Ni/Zr co-doping strategy to promote cyclic performance of CaO-based materials for thermochemical energy storage: Experimental and first-principles insights - Zhu-yu Li; Le-ran Li; Jing-yi Liu; Qi Niu; Zhi-mo Fang; Ji-hong Li; Kai Li; Qiang Lu (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Slow-release ferrous effects on synchronous stabilization of lead, cadmium, and arsenic in soil - Zhi Jiang; HongZhen Ran; Lin Yu; Mei Jiang; Weichun Yang (Environmental Geochemistry and Health, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

A novel dual-emission fluorescence sensor with different responsive modes for non-invasive and simultaneous quantitative detection of carbaryl and imidacloprid - Yi-Fan Xia; Hou-Qun Yuan; Zhi-Qiang Cai; Le Fang; Zhen-Chong Dou; Qian-Wen Yang; Yi-Xuan Hu; Ran Wang; Yu-Fei Zhong; Guang-Ming Bao (Chemical Engineering Journal, 2025)

Suitable water management improving cold tolerance of rice seedlings - Qiang Zhang; Feng Wen; Bingbing Li; Zhi Li; Zhenjiang Wu; Xu Kuang; Guilong Yu; Xiangchen Liu; Yang Hu; Yuchen Zhang; Ran Yu; Lingling Ding; et al. (Cereal Research Communications, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Pagoda solar evaporators with an alternating hot-cold pattern for rapid, scaling-free desalination of hypersaline brines - Zhenwei Wu; Kai Li; Ran Deng; Yu-Ren Xue; Hao-Nan Li; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2024)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Taming the anchor and conversion of polyselenides with a self-reinforcing host in lithium–selenium batteries - Hongyan Li; Wenda Dong; Yueqiang Cao; Tarek Barakat; Marvin Laboureur; Mao-Jin Ran; Zhi-Yi Hu; Hongxian Zhang; Cheng-Bin Jin; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Uptake, subcellular distribution, and fate of tetracycline in two wetland plants supplemented with microbial agents: Effect and mechanism - Jie Zhong; Hang Wei; Jian-Xiong Xie; Yu-Hui Wu; Bing Tang; Qi Zou; Peng-Ran Guo; Zhi-Liang Chen (Journal of Environmental Management, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Simultaneous determination of twelve natural estrogens in dairy milk using liquid–liquid extraction and solid-phase extraction coupled with gas chromatography-mass spectrometry - De-ming Kong; Zhao Tang; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Yu Liu (Environmental Science and Pollution Research, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Chloroacetonitrile exposure induces endoplasmic reticulum stress and affects spindle assembly in mouse oocytes - Feng-Xin Qiao; Ming-Xin Sun; Zhi-Ran Xu; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Cobalt chloride exposure disturbs spindle assembly and decreases mouse oocyte development potential - Si-Cheng Zhao; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhi-Ran Xu; Yu Liu (Toxicology, 2023)

Triptolide exposure induces oxidative stress and decreases oocyte quality in mouse - Qian-Qian Hao; Zhi-Ran Xu; Han Nie; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Toxicon, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Maximum displacement prediction of composite floor system under falling impact - Jing-Zhou Zhang; Guo-Qiang Li; Ying-Zhi Sun; Jing Sun; Zhi-Wei Yu; Ran Feng (Engineering Structures, 2023)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Numerical simulation of dynamic responses of semi-rigid rockfall protection barriers subjected to impact loading at different positions - Xin Qi; Lei Zhao; Chao-Ran Hao; Zhi-Xiang Yu; Shi-Chun Zhao (Bulletin of Engineering Geology and the Environment, 2022)

Deduction and exploration of the evolution and function of vertebrate GFPT family - Si-ang Wei; Ran Xu; Yu-yao Ji; Zhi-wen Ding; Yun-zeng Zou (Genes & Genomics, 2022)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Construction of a recombinant BHV-1 expressing the VP1 gene of foot and mouth disease virus and its immunogenicity in a rabbit model - Xian-Gang Ren; Fei Xue; Yuan-Mao Zhu; Guang-Zhi Tong; Yan-Hui Wang; Jun-Ke Feng; Hong-Fei Shi; Yu-Ran Gao (Biotechnology Letters, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)